Acute Coronary Syndrome follow up: Portuguese experience. (11th May 2021) - Santos, H; Miranda, H; Santos, M; Almeida, I; Sa, C; Chin, J; Almeida, S; Sousa, C; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Portuguese Registry of Acute Coronary Syndromes Background: Acute coronary syndrome is a major health problem, with several acute and chronic complications. So, it is imperative identifying factors that can be associated with better and worse prognosis during the follow up these patients. Objective: Evaluate predictors of mortality, cardiovascular readmission and all causes of readmission at 1 year follow up in ACS patients. Methods: Multicenter retrospective study, based on the Portuguese Registry of ACS between 1/10/2010-4/09/2019. Logistic regression was performed to assess predictors of mortality, cardiovascular readmission and all causes of readmission at 1 year follow up in ACS patients. Results: 1492 patients were included, 141 die during the first year. Age > 75 years old (odds ratio (OR) 2.557, p < 0.001, confidence interval (CI) 1.727-3.785), heart rate < 60 (OR 2.686, p = 0.008, CI 1.296-5.569), cardiogenic shock (OR 6.726, p = 0.012, CI 1.512-29.915), creatinine >2mg/dL (OR 1.956, p = 0.023, CI 1.099-3.480), left ventricular ejection fraction <50% (OR 1.911, p = 0.001, CI 1.284-2.844), nitrate (OR 1.589, p = 0.020, CI 1.074-2.351), ivabradine (OR 1.831, p = 0.011, CI 1.146-2.924), aldosterone antagonists (OR 1.632, p = 0.020, CI 1.079-2.468), diuretic (OR 1.625, p = 0.023, CI 1.069-2.472) and mechanical complication d (OR 55.518, p < 0.001, CI 11.516-267.655) were predictors of mortality of 1 year of follow up. Regarding cardiovascular readmission was registered in 291 patients, of a total 1412. Were predictors of cardiovascular readmission previous history of heart failure (OR 1.467, p = 0.003, CI 1.135-1.895), cardiogenic shock (OR 3.447, p = 0.039, CI 1.068-11.128), acetylsalicylic acid previous to ACS (OR 1.751, p = 0.008, CI 1.285-2.385), multivessel disease (OR 1.667, p = 0.002, CI 1.206-2.306), left ventricular ejection fraction <50% (OR 1.489, p = 0.003, CI 1.145-1.938), nitrate (OR 1.812, p < 0.001, CI 1.403-2.341), aldosterone antagonists (OR 1.572, p = 0.004, CI 1.155-2.140) and sustained ventricular tachycardia (OR 55.518, p < 0.001, CI 11.516-267.655). On the other hand 411 patients was readmitted (all causes), in 1455 patients with follow up. Were predictors of all causes of readmission previous history of heart failure (OR 1.347, p = 0.025, CI 1.039-1.747), previous chronic obstructive pulmonary disease (OR 1.456, p = 0.041, CI 1.016-2.087), atrial fibrillation (OR 1.439, p = 0.027, CI 1.041-1.988), acetylsalicylic acid previous to ACS (OR 1.473, p = 0.001, CI 1.161-1.869), left ventricular ejection fraction <50% (OR 1.456, p = 0.001, CI 1.166-1.819), nitrate (OR 1.478, p < 0.001, CI 1.192-1.831), aldosterone antagonists (OR 1.493, p = 0.003, CI 1.148-1.943) and sustained ventricular tachycardia (OR 3.792, p = 0.004, CI 1.540-9.337). Conclusions: Left ventricular ejection fraction <50%, nitrate as discharge therapeutic and aldosterone antagonists as discharge therapeutic were predictors of mortality, cardiovascular readmission and readmission for all causes at 1 year follow up.